The library at night - Manguel, Alberto (New Haven, CT : Yale University Press, 2008)
Inspired by the process of creating a library for his home near the Loire, in France, Alberto Manguel, writer on books and reading, has taken up the subject of libraries. "Libraries have always seemed to me pleasantly mad places, and for as long as I can remember I've been seduced by their labyrinthine logic." In this personal, deliberately unsystematic, and wide-ranging book, he offers a meditation on the meaning of libraries. Manguel, a guide of irrepressible enthusiasm, conducts a unique library tour that extends from his childhood bookshelves to the Internet, from Ancient Egypt and Greece to the Arab world, from China and Rome to Google. He ponders the personal libraries of Charles Dickens, Jorge Luis Borges, and others. He recounts stories of people who have struggled against tyranny to preserve freedom of thought, oral "memory libraries" kept alive by prisoners, libraries of banned books, and the library of books never written.--From publisher description
The library as myth -- The library as order -- The library as space -- The library as power -- The library as shadow -- The library as shape -- The library as chance -- The library as workshop -- The library as mind -- The library as island -- The library as survival -- The library as oblivion -- The library as imagination -- The library as identity -- The library as home.
Includes bibliographical references (pages 329-356) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Libraries; Libraries -- History; Books and reading -- History; Bibliothèques.; Bibliothèques -- Histoire; Livres et lecture -- Histoire; libraries (buildings); LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Archives & Special Libraries; LITERARY COLLECTIONS -- General; Books and reading; Libraries; History